2000
DOI: 10.1291/hypres.23.239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coronary Blood Flow on Left Ventricular Function in Essential Hypertensive Patients.

Abstract: To elucidate the mechanism of left ventricular dysfunction associated with left ventricular hypertrophy in hypertension, coronary blood flow (CBF) and left ventricular mass (LVM) were measured in 62 patients with essential hypertension (mean age, 54 ± 13 years) and 22 normotensive control subjects (mean age, 57 + 13 years). According to the indicator fractionation principle, CBF/cardiac output (CO), estimated on the basis of the ratio of myocardial uptake/total injected dose of thallium-201 (% cardiac uptake),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
2
16
0
3
Order By: Relevance
“…In our study, RWT was significantly correlated with-and LVMI tended to correlate with-the CFR, and the basal coronary flow in hypertensive patients was increased to the same degree as in previous studies (10,25). It has been suggested that remodeling of the coronary arterioles, an increase in the extracellular matrix, and increased oxygen demand following established LVH are all strong contributors to the impairment of CFR in patients with hypertension (26,27). However, when the analysis was limited to hypertensive patients in our study, CFR did not correlate with LVMI or RWT.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, RWT was significantly correlated with-and LVMI tended to correlate with-the CFR, and the basal coronary flow in hypertensive patients was increased to the same degree as in previous studies (10,25). It has been suggested that remodeling of the coronary arterioles, an increase in the extracellular matrix, and increased oxygen demand following established LVH are all strong contributors to the impairment of CFR in patients with hypertension (26,27). However, when the analysis was limited to hypertensive patients in our study, CFR did not correlate with LVMI or RWT.…”
Section: Discussionsupporting
confidence: 81%
“…2.7 Our findings showed that lower CFR was significantly and independently associated with lower resting stress-corrected MWS, a measure of myocardial contractility. Previously, it was reported an association of lower MWS with lower resting myocardial blood flow assessed by SPECT, 35 but CFR was not tested. Lower myocardial contractility may be associated with lower coronary blood flow; however, the association of lower resting myocardial contractility to lower CFR by dipyridamole stress testing is new.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia reflected by the decrease in unit coronary blood flow might be closely related to LV dysfunction in patients with essential hypertension (3). Angiotensin (Ang) II cardial ischemia (6), and decreasing coronary artery periarteriolar collagen deposition in hypertension (7,8).…”
Section: Introductionmentioning
confidence: 99%